2006
DOI: 10.1016/j.leukres.2005.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib (Velcade) for progressive myeloma after autologous stem cell transplantation and thalidomide

Abstract: Twenty-one patients with multiple myeloma, all relapsed after frontline autologous stem cell transplantation and all relapsed again after or resistant to thalidomide (employed as second line treatment) received bortezomib (1.3 mg/m 2 body surface twice weekly for 2 weeks followed by an interval of 10-12 days) without adjunct of steroids as third line therapy. Three patients died of progressive disease during the first 2 cycles with bortezomib. Eighteen patients received at least 2 cycles and were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Accordingly, new strategies are required to reduce both the risk of relapse and the toxicity of the procedure. Bz has been studied in the context of relapse after autologous SCT, showing a response rate of 35% to 43% (Richardson et al , ; Musto et al , ). Also a phase II study showed that Bz and dexamethasone followed by donor lymphocyte infusion is safe, resulting in an ORR of 68% (20% CR) (Montefusco et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, new strategies are required to reduce both the risk of relapse and the toxicity of the procedure. Bz has been studied in the context of relapse after autologous SCT, showing a response rate of 35% to 43% (Richardson et al , ; Musto et al , ). Also a phase II study showed that Bz and dexamethasone followed by donor lymphocyte infusion is safe, resulting in an ORR of 68% (20% CR) (Montefusco et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is approved for the treatment of multiple myeloma (25,32,33). Bortezomib's mechanism of antitumor activity, however, is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib is a selective inhibitor of the 26S proteasome and has been approved for the treatment of multiple myeloma (25). Preclinical and early clinical data suggest that bortezomib also has significant antitumor activity in other types of cancer, including squamous cell cancer (SCC) of the head and neck (HNSCC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found to induce high quality responses as third line salvage therapy with acceptable toxicity in a significant proportion of homogeneously pre-treated myeloma patients with progressive disease after autologous transplantation and thalidomide. [119]. In a Phase 3 trial involving 669 myeloma patients treated with at least one prior therapy, bortezomib increased median, improved overall survival, and increased response rate, compared with high-dose dexamethasone [120].…”
Section: Monoclonal Antibody Therapiesmentioning
confidence: 99%